Guru Sebagai Pilar Utama Pembentukan Karakter - Musfirah, Nurul; N, Nurbaya; Buka, Nurhan; Alimudin, Akhyar; Hamzah, Andi Abdul (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Teacher are role models, both in terms of knoqlwdge and personality for for their students. The role of teachers is stated in Article 3 of Law no. 20 of 2003 concerning the National Education System, which states that national education functions to develop abilities and shape the character and civilization of a dignified nation in order to educate the life of the nation, and aims to develop the potential of students to become human beings who believe and are devoted to God Almighty. , have noble character, be healthy, knowledgeable, capable, creative, independent, and be a democratic and responsible citizen. The characters in Greek and Latin come from the word charassein which means to carve a permanent and indelible pattern. Character or character is a combination of all permanent human traits so that it becomes a special sign to distinguish one person from another. Individuals with good character are individuals who can make decisions and are ready to take responsibility for all the consequences of the decisions they make. There are three stages of character formation, namely: Moral knowing, namely a good understanding in children about the meaning of goodness. Moral feeling, namely building love for good behavior in children which will become a source of energy for children to behave well. Moral feeling is strengthening students' emotional aspects so that they become human beings with character. This strengthening is related to the form of attitude that must be felt by students, namely awareness of identity, self-confidence, sensitivity to other people's suffering, love of truth, self-control and humility. Moral action, namely how to change moral knowledge into real action.